Desenvolvimento de estratégias de gestão de sala de aula no PIBID artes visuais: pesquisa e intervenção em clínica da atividade - Rodrigues, Lilian (2017)
This study presents results related to the development of classroom management strategies within initial educational formation by the Visual Arts PIBID Program at the Federal Institute of Paraná, campus Palmas. For the research an intervention was carried out, utilizing the Activity Clinic Methodology by Vigotsky and Bakhtin (CLOT, 2007/2010), taking place during the Art classes at the Colégio Estadual Alto Glória. Utilizing the simple and crossed self-confrontation method (FAÏTA, 1996; CLOT, 2007/2010) it was verified that the problem is the adaptations the pair of under formation teachers conducted in their work. For the theoretical foundation it is presented a discussion between rationalization through instrumental technique and complex totality mode (MORIN, 2005; RAYNALT, 2004; LEFF, 2010), presenting the Activity Clinic as an alternative for this second model. We searched for the relation between the University and the public school in Santos (1997/2010); in Bakhtin‟s linguistic (2011/2016) the concepts of thematic content, composition construction, style and architectonics; in Vigotsky‟s psychology (1998/2007), the concept of zone of proximal development (ZPD); in Guérin et al.‟s ergonomics (2004) the concepts of prescript work and real work that are also utilized in educational activity by Souza-e-Souza (2014). For the analysis of the data produced in the classes and in the simple and crossed self-confrontation, we utilized, besides the already mentioned theories, the concept of class management (GAUTHIER ET AL. 1998); the concept of attention as high mental function (VIGOTSKY, 2001) and the perspective of discussion as a way of learning (PONTECORVO, 2005). From the data analysis it is verified that even in the midst of public school adversities, the under formation teachers found management class alternatives, thinking of questions related to the learning process, such as the students‟ attention, discussion, apperception and interest on their proposes. The data observation shows the PIBID program as a resource capable of making the public school precariousness visible. The program also allows the training of new teachers in practical teaching situations. Through the implementation of Activity Clinic it was possible to observe a rationality change in the way the teachers conducted their classes. This raising of consciousness and the critics brought by the teachers represent an indicative of the effort for changing and for a new perspective for the public school.